2016
DOI: 10.21273/hortsci.51.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of South African Bottle Gourd [Lagenaria siceraria (Molina) Standl.] Landraces Revealed by Simple Sequence Repeat Markers

Abstract: Bottle gourd [Lagenaria siceraria (Molina) Standl.] landraces are widely grown in South Africa, and genetic diversity analysis is necessary to identify promising genotypes for breeding or systematic conservation. Sixty-seven diverse bottle gourd landraces were genotyped using 14 selected simple sequence repeat (SSR) markers. The number of alleles detected per marker ranged from 4 to 11, with a total of 86 putative alleles being amplified. Allele sizes ranged from 145 to 330 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
3
21
1
Order By: Relevance
“…Based on population structure analysis, two genetically differentiated groups were identi ed; the rst including all the accessions originated from South Africa and the second group comprising of Asian and Chilean accessions. These results agree with previous studies conducted in bottle gourd, which reported that clustering of different landraces was independent of geographical location(Yetişir et al 2008;Sarao et al 2014;Gürcan et al 2015;Mashilo et al 2016b). Another explanation is that founder effect followed by arti cial selection based on fruit shape which tend to generate high genetic similarity(Xu et al 2011;Yildiz et al 2015).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Based on population structure analysis, two genetically differentiated groups were identi ed; the rst including all the accessions originated from South Africa and the second group comprising of Asian and Chilean accessions. These results agree with previous studies conducted in bottle gourd, which reported that clustering of different landraces was independent of geographical location(Yetişir et al 2008;Sarao et al 2014;Gürcan et al 2015;Mashilo et al 2016b). Another explanation is that founder effect followed by arti cial selection based on fruit shape which tend to generate high genetic similarity(Xu et al 2011;Yildiz et al 2015).…”
supporting
confidence: 93%
“…2015; Mashilo et al 2016b;Ibrahim, 2021). In this study, the accessions of bottle gourd were collected from Chile, Japan (Philippines, South Korea), and South Africa.…”
Section: Bottle Gourd Ssr Locus Identi Cation and The Frequency Of Ssrsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA molecular marker technique showing polymorphism at the DNA level is a powerful tool for the characterization of germplasms (Queiroz et al, 2015), the identification of cultivars (Gross et al, 2012;Semagn et al, 2006), and the estimation of genetic diversity (Mashilo et al, 2016;Parveen et al, 2016;Urrestarazu et al, 2015). Among the various DNA-based molecular markers, simple sequence repeats (SSRs), with the advantages of codominance inheritance, a high degree of polymorphism, reproducibility, and simple operation (Sefc et al, 2001), have been widely used in genetic diversity analyses of grape cultivars and the identification of germplasms (Emanuelli et al, 2013;Guo et al, 2010;Marinoni et al, 2009;This et al, 2004;Villano et al, 2014).…”
mentioning
confidence: 99%